Adaptive dead-time compensation for grid-connected PWM inverters of single-stage PV systems - Herrán, Mario Alejandro (2013)
This study presents a new software-based plug-in dead-time compensator for grid-connected pulsewidth modulated voltage-source inverters of single-stage photovoltaic (PV) systems using predictive current controllers (PCCs) to regulate phase currents. First, a nonlinear dead-time disturbance model is reviewed, which is then used for the generation of a feed-forward compensation signal that eliminates the current distortion associated with current clamping effects around zero-current crossing points. A novel closed-loop adaptive adjustment scheme is proposed for fine tuning in real time the compensation model parameters, thereby ensuring accurate results even under the highly varying operating conditions typically found in PV systems due to insolation, temperature, and shadowing effects, among others. The algorithm implementation is straightforward and computationally efficient, and can be easily attached to an existent PCC to enhance its dead-time rejection capabilitywithout modifying its internal structure. Experimental results with a 5-kW PV system prototype are presented.